ASSESSMENT OF THE STATUS AND SELECTION OF THE SOLUTIONS FOR RE-DESIGN AND CONSOLIDATION OF SOME OFFSHORE STEEL JACKET STRUCTURES ON THE CORAL AND MADREPORE BASIS - Cuong, Dinh Quang (Vietnam Journal of Marine Science and Technology, 2006)
ASSESSMENT OF THE STATUS AND SELECTION OF THE SOLUTIONS FOR RE-DESIGN AND CONSOLIDATION OF SOME OFFSHORE STEEL JACKET STRUCTURES ON THE CORAL AND MADREPORE BASIS